Drying in the process industry - Land, C. M. van't, 1937- (Hoboken, N.J. : John Wiley & Sons, 2012)
"This book assists the process development engineer, the process engineer, and the plant engineer in selecting drying equipment. The criteria to be observed are discussed. The procedure concerning the selection of an industrial dryer always starts with the gathering of results of relevant laboratory measurements. The next step is carrying out small-scale tests, the results of which can be scaled up. Procedures for sizing equipment are also covered. Written by an author with over four decades in the process industries, this book brings an extensively practical approach for the engineer"--
Includes bibliographical references and index.
"Written by an author with over four decades in the process industries, this book takes a practical approach for the working engineer. It assists him or her in selecting drying equipment by explaining dryer basics, criteria, selection procedure, and sizing. The coverage also describes a diverse array of drying equipment (convective, fluid-bed, direct-heat, flash, spray, batch, and steam) from an engineer's perspective. It provides ready access to drying technologies with references to more detailed literature. Finally, the book treats drying as part of an integrated process in the production process"-- Provided by publisher.
Machine generated contents note: Preface.Acknowledgements.1.Introduction.2. Drying as Part of the Overall Process.3. Procedures for choosing a dryer.4. Convective drying.5. Continuous Fluid-Bed Drying.6. Continuous Direct-Heat Rotary Drying.7. Flash Drying.8. Spray Drying.9. Miscellaneous Continuous Convective Dryers and Convective Batch Dryers.10. Atmospheric contact dryers.11. Vacuum drying.12. Steam Drying.13. Radiation Drying.14. Product Quality and Safeguarding Drying.15. Continuous Moisture-Measurement Methods, Dryer Process Control, and Energy Recovery.16. Gas/Solid Separation Methods.17. Dryer Feeding Equipment.List of symbols.Index.
Keywords: Drying; Drying apparatus; Chemical processes; TECHNOLOGY & ENGINEERING / Chemical & Biochemical